2020
DOI: 10.35469/ak.2020.242
|View full text |Cite
|
Sign up to set email alerts
|

Eating attitudes and body image concerns among female athletes from aesthetic sports

Abstract: Purpose: Research has suggested that in female athletes from aesthetic sports the prevalence of disordered eating attitudes is higher than in female athletes from other sports, mainly due to sport related factors like extreme training and practicing sports associated with high pressure and the idea that “being thin leads to success”. The study was conducted to examine the prevalence of disturbed eating attitudes and their relationship with body image concerns in aesthetic and non-aesthetic female athletes. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Similar findings were reported for sport-related body dissatisfaction. BMI showed a significant positive association with sport-related body dissatisfaction in all three (100%) studies that assessed this outcome ( Voelker et al, 2014 , 2018 ; Aleksic-Veljkovic and Djurovic, 2020 ).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Similar findings were reported for sport-related body dissatisfaction. BMI showed a significant positive association with sport-related body dissatisfaction in all three (100%) studies that assessed this outcome ( Voelker et al, 2014 , 2018 ; Aleksic-Veljkovic and Djurovic, 2020 ).…”
Section: Resultsmentioning
confidence: 91%
“…Eleven of the 22 studies (50.0%) assessing an aspect of negative body image had all-female participants ( Karr et al, 2013 ; Voelker et al, 2014 ; de Sousa Fortes et al, 2015b , 2020 ; Aleksic-Veljkovic and Djurovic, 2020 ; Whitehead et al, 2020 ; Eufrásio de Medeiros et al, 2021 ; Godoy-Izquierdo and Díaz, 2021 ; Remmel et al, 2021 ; Jardim et al, 2022 ; Kagawa et al, 2023 ), while four (18.2%) included only males ( Goltz et al, 2013 ; de Sousa Fortes et al, 2015a ; Hernández-Martínez et al, 2017 ; Voelker et al, 2018 ). All but one ( Remmel et al, 2021 ) of these studies reported significant positive associations between BMI, skinfolds or %BF and an aspect of body image disturbance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations